A role for T‐cell exhaustion in Long COVID‐19 and severe outcomes for several categories of COVID‐19 patients. Issue 10 (19th July 2021) - Roe, Kevin
Abstract: Unusual mortality rate differences and symptoms have been experienced by COVID‐19 patients, and the postinfection symptoms called Long COVID‐19 have also been widely experienced. A substantial percentage of COVID‐19‐infected individuals in specific health categories have been virtually asymptomatic, several other individuals in the same health categories have exhibited several unusual symptoms, and yet other individuals in the same health categories have fatal outcomes. It is now hypothesized that these differences in mortality rates and symptoms could be caused by a SARS‐CoV‐2 virus infection acting together with one or more latent pathogen infections in certain patients, through mutually beneficial induced immune cell dysfunctions, including T‐cell exhaustion. A latent pathogen infection likely to be involved is the protozoan parasite Toxoplasma gondii, which infects approximately one third of the global human population. Furthermore, certain infections and cancers that cause T‐cell exhaustion can also explain the more severe outcomes of other COVID‐19 patients having several disease and cancer comorbidities.